THE OF RELIGION ON THE INTERNATIONAL RELATIONS IN THE XXI CENTURY - Пода, Т. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article analyzes the role of the religion and its influences on the international relations in the XXI century.